(untitled) (Proceedings of the International Conference on Public Health, 2017)
People with intellectual disabilities (ID) may face multiple disadvantages regarding their physical and mental health. They tend to are more vulnerable to risks of illness (associated with their impairment, medication intake or social determinants, like low socio-economic status) and are confronted with various barriers in health care and health promotion (e. g. communication or programmatic barriers). This study aims to gain a better understanding of the health-relevant factors people with ID experience in their everyday life in an urban area in Germany. An inclusive research workshop was held at the Catholic University of Applied Sciences Berlin. Ten adults with ID and six members of the university (two students, four academic researchers) joined the workshop and worked together as a research group. Photovoice, a participatory research methodology, was utilized. The research group collected data by taking photographs and discussing the pictures within the group. This process resulted in a set of qualitative categories and themes. The health-relevant factors identified were multifaceted. They ranged from housing and working conditions to the effects of keeping pets or being affected by racism and discrimination. The findings were prepared in form of an exhibition, providing a basis for developing municipal strategies for inclusive health promotion.